2020
DOI: 10.1097/jhq.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Improving Timeliness of Internal Medicine Consults in the Emergency Department: A Quality Improvement Initiative

Abstract: Introduction: Emergency department (ED) wait time is an important health system quality indicator. Prolonged consult to decision time (CTDT), the time it takes to reach a disposition decision after receiving a specialty consultation request, can contribute to increased overall length of stay in the ED. Objective: To identify delays in the consultation process for general internal medicine (GIM) and trial interventions to reduce CTDT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The majority of the included studies were conducted in North America (United States n = 12, 16–28 Canada n = 6 29–34 ) with a smaller number of studies conducted in Asia (South Korea n = 5, 35–39 Singapore n = 2, 40,41 Thailand n = 1, 42 Taiwan n = 1, 43 India = 1 44 ) and Europe (Ireland n = 1, 45 Turkey n = 2, 46,47 ; see Table 1). The studies were mainly conducted in a single ED site 16–25,27,29–32,34–50 . The majority of studies utilized a before/after study design ( n = 25, 71%), of which one study used a controlled before/after design 39 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the included studies were conducted in North America (United States n = 12, 16–28 Canada n = 6 29–34 ) with a smaller number of studies conducted in Asia (South Korea n = 5, 35–39 Singapore n = 2, 40,41 Thailand n = 1, 42 Taiwan n = 1, 43 India = 1 44 ) and Europe (Ireland n = 1, 45 Turkey n = 2, 46,47 ; see Table 1). The studies were mainly conducted in a single ED site 16–25,27,29–32,34–50 . The majority of studies utilized a before/after study design ( n = 25, 71%), of which one study used a controlled before/after design 39 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, five studies reported completing audits and providing feedback in regard to responding to consultation requests and timely admission decisions to the staff and health administers 17,19,20,29,31 . Two of the studies that audited physician performance also provided staff with educational sessions on ED overcrowding (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations